Neonatal handling prevents anxiety-like symptoms in rats exposed to chronic mild stress: Behavioral and oxidative parameters. (May 2013) - Boufleur, Nardeli; Antoniazzi, Caren T.D.; Pase, Camila S.; Benvegnú, Dalila M.; Dias, Verônica T.; Segat, Hecson J.; Roversi, Katiane; Roversi, Karine; Nora, Magali Dalla; Koakoskia, Gessi; Rosa, João G.; Barcellos, Leonardo J.G.; et al.
<x xml:space="preserve">Abstract</x> This study investigated the influence of neonatal handling on behavioral and biochemical consequences of chronic mild stress (CMS) in adulthood. Male rat pups were submitted to daily tactile stimulation (TS) or maternal separation (MS), from postnatal day 1 (PND1) to postnatal day 21 (PND21), for 10 min/day. In adulthood, half the number of animals were exposed to CMS for 3 weeks and submitted to behavioral testing, including sucrose preference (SP), elevated plus maze (EPM), and defensive burying tasks (DBTs), followed by biochemical assessments. CMS reduced SP, increased anxiety in EPM and DBT, and increased adrenal weight. In addition, CMS decreased plasma vitamin C (VIT C) levels and increased protein carbonyl (PC) levels, catalase (CAT) activity in hippocampus and cortex, and superoxide dismutase (SOD) levels in cortex. In contrast, both forms of neonatal handling were able to prevent reduction in SP, anxiety behavior in DBT, and CMS-induced adrenal weight increase. Furthermore, they were also able to prevent plasma VIT C reduction, hippocampal PC levels increase, CAT activity increase in hippocampus and cortex, and SOD levels increase in cortex following CMS. Only TS was able to prevent CMS-induced anxiety symptoms in EPM and PC levels in cortex. Taken together, these findings show the protective role of neonatal handling, especially TS, which may enhance ability to cope with stressful situations in adulthood.